Ideology : an introduction - Eagleton, Terry, 1943- (London ; New York : Verso, 1991)
Terry Eagleton unravels the many different definitions of ideology, and explores the concept's torturous history from the Enlightenment to postmodernism. The book provides lucid accounts of the thought of key Marxist thinkers, as well as of Schopenhauer, Nietzsche, Freud and the various post-structuralists.
Includes bibliographical references (p. 225-233) and index.
Keywords: Ideology -- History